DNA Encapsidation and Capsid Assembly Are Underexploited Antiviral Targets for the Treatment of Herpesviruses - Keil, Tara; Liu, Dongmei; Lloyd, Megan; Coombs, Wanda; Moffat, Jennifer; Visalli, Robert (Frontiers in Microbiology, 2020)
Although there are effective nucleoside analogs to treat HSV, VZV and HCMV disease, herpesvirus infections continue to contribute to significant morbidity and mortality. Acyclovir is the drug of choice for HSV encephalopathy, yet there is an estimated 6-19% mortality rate with half of the survivors experiencing moderate to severe chronic neurological deficits. For VZV, current treatments are inadequate to prevent acute and persistent pain due to zoster. Treatment of HCMV with GCV requires close monitoring particularly in patients with impaired renal function and there are no approved treatments for congenital HCMV infections. New therapeutic options to control cytomegalovirus reactivation in bone marrow and stem cell transplant patients are needed to improve patient outcome. No successful chemotherapeutic options are available for EBV, HHV-6, 7, and 8. Drug resistance is a concern for HCMV, HSV, and VZV since approved drugs share common mechanisms of action. Targeting DNA encapsidation or capsid assembly provide additional options for the development of non-nucleoside, small molecule anti-herpesviral drugs.